CO2-induced asphaltene deposition and wettability alteration on a pore interior surface. (15th October 2019) - Li, Xingxun; Chi, Pengcheng; Guo, Xuqiang; Sun, Qiang
Abstract: CO2 enhanced oil recovery has a great potential to improve the rate of oil production and store carbon dioxide emission. However, CO2 injection can destabilize the asphaltene-oil colloidal system and thus favor severe asphaltene particle deposition in porous reservoir formation. These block reservoir pores and change pore wetting condition, finally damage the porous reservoir formation and significantly reduce oil production. A good understanding on CO2 -induced asphaltene deposition at a pore scale is of significance for CO2 -EOR processes. Few studies have directly investigated the asphaltene deposition behavior and asphaltene-induced pore wetting alteration on a pore interior surface in a confined pore. In this study, we directly measured the CO2 -induced asphaltene deposition behavior on the interior surface of a single pore under high pressure and temperature. The particle size and particle size distribution of CO2 -induced asphaltene deposition on pore interior surfaces were directly measured and analyzed, by considering the influences of aging time and temperature. The results indicate that long aging period and elevated temperature could favor CO2 -induced asphaltene flocculation and deposition on pore interior surfaces. Finally, the pore-scale wetting alteration caused by asphaltene deposition was quantified by direct pore contact angle measurements.